Empirical Analysis of Stock Markets That Are More Prone To Losses: A Standard Coverage Test Approach - Enow, Samuel Tabot (Dinasti Publisher, 2023)
Stock market losses have been a recurring phenomenon in financial markets with far reaching implications for investors as it directly impacts the value of their portfolios and potentially jeopardizing retirement savings leading to a loss of income. Identifying stock markets that may realise less returns on investments has been critical area for portfolio managers and active market participants. Therefore, the aim of this study was to empirically investigate financial markets that are prone to losses in order to safeguard and protect investments. A standard coverage test analysis was applied in five selected markets for a sample period from June 7, 2018 to June 7, 2023. This coverage test was used to identify stock markets that breached their generalised indicators and expected losses. The findings revealed that stock market losses are significantly higher in the CAC 40 and Nikkei 225. This was evident in the significant risk violations from their expected levels. By implication, investors willing to invest in the CAC 40 and Nikkei 225 are advised to use sector diversification strategies, stop-loss orders and long term investment strategy to mitigate some of these losses.